Effect of zoledronic acid on tartrate-resistant acid phosphatase isoform type 5b and other bone markers in lung cancer patients with bone metastases - Zhang W; Rabinowits G; Laber DA; Kloecker GH (Dove Medical Press, 2012)
Wenqing Zhang1, Guilherme Rabinowits2, Damian Laber3, Goetz H Kloecker11James Graham Brown Cancer Center, University of Louisville, Louisville, KY, 2Dana-Farber Cancer Institute, Boston, MA, 3Division of Hematology/Oncology, University of Oklahoma, Tulsa, OK, USABackground: Up to 44% of lung cancer patients eventually develop bone metastases. Zoledronic acid has been shown to prevent skeletal-related complications in these patients. Bone metabolic markers play an important role in the prediction and diagnosis of bone metastasis. Measurement of serum tartrate-resistant acid phosphatase (TRAP) type 5b and other markers of bone formation and resorption might determine the response of bone metastasis to zoledronic acid therapy. Here we report the effect of zoledronic acid on bone metabolic markers in lung cancer patients.Methods: Patients with lung cancer metastatic to bone undergoing monthly treatment with zoledronic acid were enrolled in this study. Serum markers of activity of bone resorption and formation were collected at baseline, during chemotherapy, before and after zoledronic acid treatment, and every 2 weeks for the first 6 weeks, and then monthly for a total of 6 months or earlier, if bone metastases progressed radiologically. Resorption markers included N-terminal telopeptide of type I collagen, TRAP type 5b, C-terminal telopeptide of type I collagen, and deoxypyridinoline. Bone-specific alkaline phosphatase was the only bone formation marker included. The data were analyzed using the linear mixed-effects model and paired t-test.Results: Twenty-eight participants were enrolled. Thirteen patients could not be evaluated because of low-quality samples (n = 7), noncompliance (n = 5), or withdrawal of consent (n = 1). During chemotherapy without zoledronic acid, levels of TRAP type 5b remained stable. Fourteen days after zoledronic acid treatment, mean N-terminal telopeptide of type I collagen, TRAP type 5b, and bone-specific alkaline phosphatase levels decreased by 41.4% (P = 0.003), 44.9% (P = 0.014), and 12.9% (P = 0.031), respectively. These markers remained significantly decreased during monthly zoledronic acid. C-terminal telopeptide of type I collagen and deoxypyridinoline levels did not change with zoledronic acid treatment.Conclusion: TRAP type 5b, N-terminal telopeptide of type I collagen, and bone-specific alkaline phosphatase levels decreased significantly with zoledronic acid treatment in lung cancer patients with bone metastasis. The rapid response of TRAP type 5b levels to bisphosphonate therapy makes it an attractive tool for monitoring the efficacy of bone-targeted therapy in lung cancer patients.Keywords: lung cancer, bone metastasis, biphosphonates, bone markers